2012
DOI: 10.1590/s0365-05962012000500028
|View full text |Cite
|
Sign up to set email alerts
|

Results of Patch-Tests from Santa Casa de Belo Horizonte Dermatology Clinic, Belo Horizonte, Brazil, from 2003 to 2010

Abstract: This Dermatology Clinic tests referred patients who have suspected allergic contact dermatitis. The patch-test results (1406 patients) from July 1 st , 2003 to June 30 th , 2010 will be reported and compared to the data from the Brazilian Contact Dermatitis Study Group (GBEDC). A standardized patch test (30 allergens) was used in all of these patients. Depending on the complaint and suspected allergen another battery was also used (cosmetic battery).The most frequent allergens of Brazilian Standard Patch Test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 4 publications
4
12
0
1
Order By: Relevance
“…2-6 This is due to its presence in preparations like vaccines, contact lenses solutions and tattoo ink, which favors the contact of the population with this substance.…”
mentioning
confidence: 99%
“…2-6 This is due to its presence in preparations like vaccines, contact lenses solutions and tattoo ink, which favors the contact of the population with this substance.…”
mentioning
confidence: 99%
“…Landeck, et al conducted a retrospective analysis of data from patient's patch tested in Germany, Austria and Switzerland (IVDK Network) between January 2001 and December 2010 and affirmed a frequency of contact sensitization to benzalkonium chloride to be 1.6% [8]. The frequency of contact sensitization to benzalkonium chloride was determined to be 1.2% in a cohort of 2,400 patients with chronic eczema tested between the years 2001 and 2009 in our department [21] and 1.85% rates in Sweden and Denmark are about 3 to 4% [4,5]. Such differences are due to variations in the availability and use of thimerosal-containing products in each country.…”
Section: Discussionmentioning
confidence: 85%
“…A group from Santa Casa of Belo Horizonte found that 14.7% of the 1,406 patients tested between 2003 and 2010 had positive thimerosal. Nevertheless, the report did not discuss the clinical relevance of the reactions [4]. Herbst, et al confirmed allergies to thimerosal in a group of patients with periorbital dermatitis in 10.2% of the patients, yet with no comment regarding relevance [7].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Demograficamente, a exemplo do observado no presente trabalho em que a amostragem de pacientes com DC foi composta predominantemente por mulheres, tanto no grupo de idosos quanto no de não idosos, outros estudos nacionais também verificaram maior número amostral de pacientes do sexo feminino com DC [10,14,15]. Em relação à idade, existem poucos trabalhos abordando os quadros alérgicos em idosos [16][17][18][19][20][21][22][23][24][25][26][27][28][29], sendo que dois estudos nacionais apontaram uma alta prevalência de manifestações cutâneas nessa faixa etária, entre as quais a DC [21] e o prurido, como sintoma isolado [22].…”
Section: Discussionunclassified